Exposition à la pollution atmosphérique liée au trafic routier et risques sanitaires - Sabine Host (VertigO)
Although ambient urban air pollution has well-established health effects, epidemiology faces many difficulties in estimating the risks due to exposure to traffic pollutants near busy roads. This review aims to summarize how exposure to traffic-related air pollution near busy roads is assessed in epidemiological studies and main findings regarding health effects.The characterization and measurement of population exposure to traffic pollution faces many difficulties. Thus epidemiological studies have used two broad categories of surrogates to assess exposure: direct measures of traffic itself such as distance of the residence to the nearest road and traffic volume and modeled concentrations of pollutant surrogates. Studies that implemented these methods showed that people living near heavy traffic road or exposed to near-road air pollution tend to report more health outcomes.Traffic-related air pollution near busy roads is the subject of increasing attention, and tends to be better characterized. However, its health impacts remain difficult to grasp, especially because of the vast diversity of approaches used in epidemiological studies. Greater consistency in the protocols would be desirable to provide better understanding of the health issue of traffic in urban areas and thus to better implement policies to protect those most at risk.